Talent Detection, Identification and Development … a swimming perspective - Rushton, C. (2003)
Swimming tends to be more organised than many other sports - at least one club in every town and frequently more than one, offering daily or twice-daily training under qualified professional coaches and regular, structured competition for all ages and abilities. Where there is a swimming pool there is a swimming club and a qualified swimming coach, most times professional and in many cases full-time. Every year more than 500 structured, monitored, controlled and officiated competitions take place at regional level and above. So why does swimming not produce a continual stream of Olympic and world medalists? A normal distribution curve, even when superimposed on the age-, ethnic- and culturally-skewed four million of New Zealand, produces enough "freaks" at the right-hand extreme to allow some degree of success on a repeated and predictable basis. Norway, with a similar size and population, finishes in the top two or three countries at every Winter Olympics and has a stated goal of being in the top two European nations in combined Summer and Winter Olympic medals1. SPARC and NZAS would benefit from studying the philosophy and method of the Norwegian Olympiatoppen organization. All talent development initiatives require at least ten years to bring to fruition. The 10,000 hours of deliberate training originally recognized by Ericsson & Charness in 19942,3 are still valid even though they have been hijacked by TID "gurus" across the world; there are still no shortcuts to success. Twenty hours a week every week for ten years is the minimum price to pay for Olympic glory. Canadian Olympic rowing coach Mike Spracklen used a "rule of thumb" which demanded 20, 30 and 40 hours per week of training for those aspiring to finalist, medalist and gold medalist level at World Championships and Olympics. Those numbers also appear a reasonable assessment for swimming. The quality of the quantity of training ("deliberateness") is, however, more important than the quantity alone and that depends almost exclusively on the quality of the coach. Support of the coach education process would be the most efficient and effective method of investment into the swimmer development process. Any talent development initiatives supported by SPARC in 2003/04 should be guaranteed for ten years, of course with periodic evaluation and assessment, because that is how long it will take to produce results; Duncan Laing did not start coaching Danyon Loader one year before the Olympics nor did he start his coaching career with Danyon Loader. Talent retention initiatives can have a more immediate impact. Talent abounds in swimming. The major problem is, difficulties also abound in retaining talented swimmers because high performance costs in New Zealand are prohibitive and rewards for high performance are negligible. We lose talented swimmers because the financial demands are too high and we lose swimmers and coaches because the financial rewards are too low. Matching dollars into the "Results Awards and Performance Bonuses" proposal would send a clear message to swimmers and coaches that SPARC understands the problems faced by athletes and is serious about solving them. So, again, why does swimming not produce a continual stream of Olympic and world medalists? One thing is for certain; it`s not about the swimmer. Swimming, as a sport, has constraints on its ability to continually produce "performances which stop New Zealander`s in the street": We need better-educated coaches, better access to training facilities and sophisticated training equipment, structured schools competitions, different types of club, regional and national competitions, residential sports schools specialising in a small number of sports, additional fulltime national staff, significant investment in upskilling all partners in sports psychology, biochemistry and land conditioning for swimming, more access to high level international competition and financial incentives big enough to enable people to change their lifestyles. Answers to some of these needs and deficiencies are already in process but, as this paper is being written, there are just over 300 days to swimming`s Olympic Trials, less than 450 to Athens `04 and just over 1,000 to Melbourne `06. Time is not on our side and other countries, already ahead of us, are investing more and more in programmes to move them even further ahead.